187k views
2 votes
Giải phương trình
tan6x nhân tan7x= -1

User Frieser
by
5.8k points

1 Answer

1 vote

Recall that

• tan(x) = sin(x) / cos(x)

• sin(x) sin(y) = - 1/2 (cos(x + y) - cos(x - y))

• cos(x) cos(y) = 1/2 (cos(x + y) + cos(x - y))

Then we can write

tan(6x) tan(7x) = (sin(6x) sin(7x)) / (cos(6x) cos(7x))

tan(6x) tan(7x) = - (cos(13x) - cos(x)) / (cos(13x) + cos(x))

Make this replacement in the original equation and simplify:

tan(6x) tan(7x) = -1

- (cos(13x) - cos(x)) / (cos(13x) + cos(x)) = -1

(cos(13x) - cos(x)) / (cos(13x) + cos(x)) = 1

cos(13x) - cos(x) = cos(13x) + cos(x)

2 cos(x) = 0

cos(x) = 0

Solving for x gives

x = π/2 + = (2n + 1)π/2

where n is any integer. However, since 2n + 1 is odd, for any odd multiple of π/2, we would end up with

tan(6 (2n + 1)π/2) = tan((2n + 1)×3π) = tan(odd multple of π/2)

since odd×odd = odd, and cos(odd multiplie of π/2) = 0, which would make tan(6x) undefined.

Therefore there are no solutions to this equation.

User Mikesol
by
5.6k points